Influence of biotic and abiotic factors on the productivity of sorts and lines of spelta wheat - Любич, В. В. (Scientific Progress & Innovations, 2017)
The results of study of forming of the productivity of sorts and lines of spelta wheat are resulted in the article. It is set that the productivity and maintenance of albumen in grain of spelta wheat depend on the weather terms of vegetation period, height of plants, stability to lodging and defeat the exciters of mycotic illnesses. The highest stability to lodging is characterize the lines of LPP 1304, P 3, LPP 1221, the productivity of which changes from 6,74 to 9,64 t/he. The table of contents of albumen in grain of spelta wheat depends on the height of plants and index of development of illnesses. High maintenance of albumen is characterize grain of sorts Zoria of Ukraine, Schwabenkorn and lines of LPP 1221, P 3 TV 1100 – 16,8–22,5 %.